Disciplining the Holocaust - Ball, Karyn 1965- (Insinuations: philosophy, psychoanalysis, literature, 2008)
Bridging the gap between psychoanalysis and Foucault's understanding of disciplinary power, this work explores the relationship between disciplinarity and contemporary ethics of scholarship about the Holocaust.